Ang alamat ng lawin ([s.l.] FPJ Production, 2003)
A gang of three boys and a girl come in for an unexpected sojourn to a strange neverland, zapped by some mysterious force where they come face to face with an adventure of a lifetime. Stumbling upon magical powers they soon after cross paths with ;the legendary warrior, Lawin. The strange ;neverland's last hope of survival against the evil armies of Draka. As the netherworldly configuration of violence and destruction dawn upon them, it likewise becomes clear. The only choice they have is for them kids to hook up with Lawin for the final battle for neveland.
Story and screenplay by Manny R. Buising ; directed by Ronwaldo Reyes
Fenando Poe Jr.;Ina Raymundo
Keywords: Feature films